SYSTACTICAL METHODS OF THE UZBEK AND ENGLISH LANGUAGE TERMINOLOGY - Jabborovich, Jabborov Khojamurod; Keldiyorovna, Omonova Makhfurat (International Journal of Psychosocial Rehabilitation, 2020)
In the terminology, the construction of a combination’s terms means that two or more terms are used to create joint and compound terms without any linguistic means.Modern Uzbek vocabulary forms are different. The first part of “Uzbek Grammar” is based on the following:1. Grammar word-making (make with affix- affixation, make with words-composition, conversion)2. Lexical-semantic word formation (formation of new word through change of meaning)3. Phonetic word formation (phonetic means, with the help of various phonetic modifications). Terminology deals with the definitions and concepts of a particular field. The development of a particular subject in relation to the human need is concrete. If this specificity makes it necessary to distinguish one of the phenomena that have similarities, then the need for separation creates the need to express the characteristics of the subject. In other words, just as each subject has similar characteristics, they also have similar differences. There are also parts of the whole and piece of that part. As a result, simple terminology and complex compound terms emerge in the terms system.